Singular and short-term anesthesia exposure in the developing brain induces persistent neuronal changes consistent with chronic neurodegenerative disease - Kaley Hogarth (Nature Portfolio, 2021)
Abstract The potential adverse impact of inhalational anesthetics on the developing brain was highlighted by the addition of a medication warning by the U.S. Food and Drug Administration for their use in the pediatric population. To investigate mechanisms by which early life anesthesia exposure could induce long-term neuronal dysfunction, we exposed rats to 1 minimum alveolar concentration sevoflurane at 7 days of life. The animals were raised normally until adulthood (P300) prior to sacrifice and analysis of cortical tissue structure (TEM), mitochondrial quality control and biogenesis pathways (Western blot, ELISA, ADP/ATP content), and markers of oxidative stress, proteotoxicity and inflammation (Western blot, ELISA). We found that early life anesthesia exposure led to adverse changes in mitochondrial quality maintenance pathways, autophagy and mitochondrial biogenesis. Although there was an escalation of oxidative stress markers and an increase in the nuclear localization of stress-related transcription factors, cellular redox compensatory responses were blunted, and oxidative phosphorylation was reduced. We found upregulation of mitochondrial stress and proteotoxicity markers, but a significant reduction of mitochondrial unfolded protein response end-effectors, contributing to an increase in inflammation. Contrary to acute exposure, we did not find an increase in apoptosis. Our findings suggest that a limited, early exposure to anesthesia may produce lasting cellular dysfunction through the induction of a sustained energy deficient state, resulting in persistent neuroinflammation and altered proteostasis/toxicity, mimicking aspects of chronic neurodegenerative diseases.